EFFECT OF WORK ENVIRONMENT AND WORKLOAD ON EMPLOYEE SATISFACTION - Astika, Enda; Nasib, Nasib; Bhastary, Manda Dwipayani; Amalia, Fiqrida; Hou, Amin (UNIVERSITAS RAHARJA, 2022)
The purpose of this study was to determine and analyze the effect both partially andsimultaneously to determine and analyze the effect of the work environment and workload on jobsatisfaction of PT Mahkota Group employees. The population in this study were all employees ofPT Mahkota Group, totaling 105 employees. The sampling technique used was purposivesampling. Where a sample of 51 employees was selected to be used as research samples. The datacollection technique used in this study was a questionnaire. The analysis technique used in thisstudy is multiple regression, classical assumptions, hypothesis testing, and coefficient ofdetermination. The results of the study indicate that there is a significant and positive effect ofwork environment variables on employee job satisfaction variables at PT Mahkota Group. There isa significant and negative effect of workload variables on employee job satisfaction variables atthe PT Mahkota Group company and there is a significant and simultaneous influence on workenvironment and workload variables on employee job satisfaction at PT Mahkota Groupcompanies. The coefficient of determination R Square is 0.615 or 61.5% where the workenvironment and workload can explain in this study while the remaining 38.5% are other variablesnot examined by this study.